Sensory and Physicochemical Properties and Stability of Folic Acid in a Pineapple Ready-to-Serve Beverage Fortified with Encapsulated Folic Acid - Geethi Pamunuwa; Harshika Nilakshi; Gagani Rajapaksha; Farrah Shakoor; Desiree Nedra Karunaratne (Journal of Food Quality)
Fortification of food and beverages with folic acid is carried out frequently as a remedy to folic acid deficiency which causes serious health issues. This study was carried out to investigate the effect of incorporation of folic acid encapsulated alginate submicron particles in pineapple ready-to-serve (RTS) beverages. The encapsulation efficiency and loading capacity of the particles were 91.54 ± 0.45% and 1.02 ± 0.01%, respectively. The photostability and thermal stability studies of folic acid revealed that encapsulation poses a protective effect on folic acid and that dark and refrigerated conditions contribute to higher stability of folic acid. In this study, sensory evaluation of the RTS beverages was carried out through both ranking tests and acceptance tests using a five-point hedonic scale. The sensory panel showed the highest preference to pineapple RTS with incorporated encapsulated folic acid at a quantity of its recommended daily intake (400 µg/200 mL) before heat treatment. Shelf-life evaluations were carried out through measuring physicochemical properties, and pH, titratable acidity, and total soluble solids showed negligible or acceptable changes over two months. Folic acid degradation occurred due to heat treatment, but encapsulation in alginate submicron particles provided heat stability to folic acid. Thus, microencapsulated folic acid may be a successful carrier of folic acid which can be incorporated in beverages such as fortified pineapple RTS.